New records of bat flies (Diptera: Nycteribiidae), with an updated checklist of the nycteribiids of Russia - Orlova, Maria V.; Klimov, Pavel B.; Moskvitina, Nina S.; Orlov, Oleg L.; Zhigalin, Alexander V.; Smirnov, Dmitriy G.; Dzhamirzoyev, Hadzhibek S.; Vekhnik, Vladimir P.; Pavlov, Alexander V.; Emelyanova, Alla A.; Khristenko, Ekaterina (Zootaxa, 2021)
We assembled a checklist by documenting and curating previously published data as well as previously unpublished records of bat flies from the Russian Federation. A total of 20 bat fly species are listed, belonging to 4 genera. Basilia mongolensis nudior Hůrka, 1972 and Basilia nattereri (Kolenati, 1857) are recorded from Russia for the first time. The following new host associations are reported: Basilia mongolensis nudior ex Myotis nattereri (Kuhl), Basilia nattereri ex Eptesicus nilssonii (Keyserling & Blasius), Basilia rybini Hůrka, 1969 ex Myotis dasycneme (Boie) and Eptesicus nilssonii, and Nycteribia quasiocellata Theodor, 1966 ex Vespertilio murinus Linnaeus. We provide data on nine major Russian regions for which nycteribiid records were previously lacking.